1993
DOI: 10.1073/pnas.90.17.7928
|View full text |Cite
|
Sign up to set email alerts
|

The primary structure of rat brain (cytoplasmic) dynein heavy chain, a cytoplasmic motor enzyme.

Abstract: Overlapping cDNA clones encoding the heavy chain of rat brain cytoplasmic dynein have been isolated. The isolated cDNA clones contain an open reading frame of 13,932 bp encoding 4644 aa (Mr, 532,213). The deduced protein sequence of the heavy chain of rat brain dynein shows significant similarity to sea urchin flageilar -dynein (27.0% identical) and toDictyostelium cytoplasmic dynein (53.5% identical) throughout the entire sequence. The heavy chain of rat brain (cytoplasmic) dynein contains four putative nudeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 24 publications
(22 reference statements)
2
47
1
1
Order By: Relevance
“…There is a clear separation between the three 13 chains and the nine cytoplasmic dyneins (bold font). Dynein heavy chain sequences and their abbreviations used in this table are as follows: DHC-6, Paramecium 13 (this study; accession number U19464); SU 13, sea urchin 13 X59603); Chlamy 13, Chlamydomonas 13 (Mitchell and Brown, 1994; U02963); Chlamy -y, Chlamydomonas y (Wilkerson et al, 1994); DHC-8, Paramecium cytoplasmic (this study; U20449); Dicty, Dictyostelium (Koonce et al, 1992;Z15124); Dro cyto, Drosophila cytoplasmic (Li et al, 1994;L23195); MAPlC, rat cytoplasmic (Mikami et al, 1993;L08505); C eleg, Caenorhabditis rhabditis (Lye et al, 1995;L33260); SU cyto, sea urchin la Z21941); N crassa, Neurospora crassa (Plamann et al, 1994;L31504); Asp, Aspergillus nidulans (Xiang et al, 1994;U03904); Yeast, Saccharomyces cerevisiae (Eshel et al, 1993;Z21877 Ogawa, 1991), Chlamydomonas (Mitchell and Brown, 1994), and Paramecium (this report); the axonemal y heavy chain from Chlamydomonas (Wilkerson et al, 1994); and the cytoplasmic dyneins from Dictyostelium (Koonce et al, 1992), rat brain (Mikami et al, 1993;Zhang et al, 1993), S. cerevisiae (Eshel et al, 1993;Li et al, 1993), Aspergillus (Xiang et al, 1994), Neurospora (Plamann et al, 1994), Drosophila (Li et al, 1994), C. elegans (Lye et al, 1995), and Paramecium (this report cated by potential differences due to species and tissue variation.…”
Section: Discussionmentioning
confidence: 89%
“…There is a clear separation between the three 13 chains and the nine cytoplasmic dyneins (bold font). Dynein heavy chain sequences and their abbreviations used in this table are as follows: DHC-6, Paramecium 13 (this study; accession number U19464); SU 13, sea urchin 13 X59603); Chlamy 13, Chlamydomonas 13 (Mitchell and Brown, 1994; U02963); Chlamy -y, Chlamydomonas y (Wilkerson et al, 1994); DHC-8, Paramecium cytoplasmic (this study; U20449); Dicty, Dictyostelium (Koonce et al, 1992;Z15124); Dro cyto, Drosophila cytoplasmic (Li et al, 1994;L23195); MAPlC, rat cytoplasmic (Mikami et al, 1993;L08505); C eleg, Caenorhabditis rhabditis (Lye et al, 1995;L33260); SU cyto, sea urchin la Z21941); N crassa, Neurospora crassa (Plamann et al, 1994;L31504); Asp, Aspergillus nidulans (Xiang et al, 1994;U03904); Yeast, Saccharomyces cerevisiae (Eshel et al, 1993;Z21877 Ogawa, 1991), Chlamydomonas (Mitchell and Brown, 1994), and Paramecium (this report); the axonemal y heavy chain from Chlamydomonas (Wilkerson et al, 1994); and the cytoplasmic dyneins from Dictyostelium (Koonce et al, 1992), rat brain (Mikami et al, 1993;Zhang et al, 1993), S. cerevisiae (Eshel et al, 1993;Li et al, 1993), Aspergillus (Xiang et al, 1994), Neurospora (Plamann et al, 1994), Drosophila (Li et al, 1994), C. elegans (Lye et al, 1995), and Paramecium (this report cated by potential differences due to species and tissue variation.…”
Section: Discussionmentioning
confidence: 89%
“…These discoveries suggested that cytoplasmic dynein may power organelle movements and perhaps mitotic movements as well. Unlike the diverse number of kinesin-related genes, thus far there appears to be but one cytoplasmic dynein heavy chain gene in most organisms (37)(38)(39)(40)(41)(42). Recent evidence suggests that cytoplasmic dynein functional diversity is achieved through the association of the heavy chain with a variety of accessory proteins that target and regulate its activity (8,43,44 (89), and epitope-tagged CIN8 or KIP1 (48,49), shows that these bimC family members are distributed along the length of spindle microtubules during mitosis.…”
Section: Potential Mitotic and Meiotic Motorsmentioning
confidence: 99%
“…Due in large part to the considerable size of dynein, the identification and characterization of cytoplasmic dyneins has not progressed as rapidly as the analyses of members of the kinesin superfamily. However, recent accomplishments in the field, most importantly the cloning of full-length dynein heavy chains from a number of organisms, have opened the door to the full characterization of cytoplasmic dynein and perhaps cytoplasmic dynein-related proteins (37,39,40,41,(73)(74)(75)(76)(77).…”
Section: Potential Mitotic and Meiotic Motorsmentioning
confidence: 99%
“…We analysed data released from the GenBank data base for cytoplasmic DHCs from rats [24,25], humans [26], D. discoideum [27], yeast [28,29], E. nidulans [30], N. crassa [31], P. tetraurelia [15], C. elegans [32], D. melanogaster [33] and sea urchins [17], and for axonemal DHCs from rats [18], P. tetraurelia [15], C. reinhardtii [12,13], D. melanogaster [16] and sea urchins [17]. The oligonucleotide primers for PCR were designed according to the amino acid sequences corresponding to the most conserved regions of the PI-loop domain among the cytoplasmic or axonemal DHC sequences, and to compensate for the potential mismatches between templates P-loops 400 aa The four centrally located P-loops are indicated by boxes 1^1 on a whole dynein heavy chain depicted by black bar, box 1 (hatched box) being the catalytic functional Pl-loop.…”
Section: Alignment Of Nucleotide Sequences and Primer Designmentioning
confidence: 99%